RF Identification and Localization - Recent Steps towards the Internet of Things in Metal Production and Processing - Vossiek, Martin; Miesen, Robert; Wittwer, Joachim (18th International Conference on Microwaves, Radar, and Wireless Communications MIKON-2010, 2010)
This paper gives an overview on recent radio frequency local positioning and identification techniques applied in steel production and processing. It is shown that it is required to combine different radio technologies in order to track and trace the goods involved in the manufacturing processes reliably and continuously. In addition the applied components must be carefully adapted to the given application area. The presented RF technologies are key components for the future internet of things and the presented applications illustrate both, the huge potential as well as the challenges involved with applying modern radio systems in harsh manufacturing processes.
lhft_intern.bib::Vossiek2010